2020
DOI: 10.1039/d0ra07392j
|View full text |Cite
|
Sign up to set email alerts
|

Oligo-glycerol based non-ionic amphiphilic nanocarriers for lipase mediated controlled drug release

Abstract: A new series of oligo-glycerol based amphiphiles have been synthesized for drug delivery.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Furthermore, the lectin binding ability was found to be sensitive towards the nature of the calixarene scaffold. The calix [4]arene skeleton had higher inhibition potential than conformationally mobile calix [8]arene. Ungaro et al reported glycocalixarenes that consisted of glucose units at the upper rim of calix [6]arene (16a) and calix [8]arene (16b), whereas the lower rim was occupied with the methyl groups (Fig.…”
Section: Reviewmentioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, the lectin binding ability was found to be sensitive towards the nature of the calixarene scaffold. The calix [4]arene skeleton had higher inhibition potential than conformationally mobile calix [8]arene. Ungaro et al reported glycocalixarenes that consisted of glucose units at the upper rim of calix [6]arene (16a) and calix [8]arene (16b), whereas the lower rim was occupied with the methyl groups (Fig.…”
Section: Reviewmentioning
confidence: 95%
“…63 The synthesized amphiphilic macrocycles selfassembled into stable vesicular aggregates in an aqueous solution that responded to pH change. The calix [8]GlcNAc and calix [8]GlyGlcNAc formed aggregates of average hydrodynamic radius of 110 nm and 200 nm, respectively revealed by static and dynamic light scattering methods. In addition, the effect of pH on the aggregation behaviour was studied with both nanostructures, as pH decreased from 7 to 3, the diameter of the aggregate of both amphiphiles decreased to 5 nm with the transition in structure from vesicle to micelles.…”
Section: Carbohydrate-based Amphiphiles As Drug/dye Nanocarriersmentioning
confidence: 98%
See 3 more Smart Citations